TUJUAN PENDIDIKAN DALAM PERSPEKTIF HADITS - Muh Kharisman; Tasmin Tangngareng (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2024)
Philosophically, all education must be based on the goals to be achieved. In the perspective of maqasidy education, the goals that become the direction of education should be oriented towards three levels of benefit, whether individual (al-shalah al-fardly), communal (al-shalal al-jama'iy), or civilization (al-shalah). al-'umraniy). This expression has an axiom, if an Islamic education process does not lead to a trilogy of benefits, then the education can be considered to have failed. To realize educational goals, you must have quality educational institutions equipped with competent educational resources. In everyday life, the indicator of achieving the goals of Islamic education is to produce students who are able to get along well with fellow humans, as well as practicing good and evil towards fellow humans. This research uses a qualitative research method accompanied by the approach used is a philosophical approach, reasoning and developing a point of view on the object of Islamic education objectives from the perspective of hadith. This type of research is library research. The main data sources are hadith books, namely the nine main hadith books (kutub altis'ah), literature on Islamic education, as well as books, research, journals and other sources that support. If you look at the hadith above, then the educational context in Abu Daud's hadith above is a hadith which includes the procedures for educating parents towards their children within the scope of religion, prayer. In this case, the Prophet expressly ordered parents to teach their children to pray when they were 7 years old, but the limit in this case is not a certainty, and it is permissible and very good if taught and introduced before that. Meanwhile, when the child is 10 years old, parents are given the legitimacy to impose a punishment if the child is reluctant to perform prayers or other religious contexts. The aim of the command above is that the author concludes that this is an illustration and effort of the Prophet to form strong principles of faith in Muslims from an early age by realizing every Shari'a. Apart from that, if it is related to several theories such as the positive August theory with a psychological approach, in substance, the hadith regarding the command to hit does not contradict logic. This is because in developmental psychology, when children are seven and eight years old, the child's awareness of their private life will increase.